Pengkajian Kemauan Membayar Cargo Service Charge (CSC) Di Bandara Ngurah Rai Denpasar - Rizki, Yuke Sri; Yuliana, Dina; Yuliawati, Eny (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
The development of air transport industry in Indonesill will have impact on the national (llJUltionbusiness. The air transport is really needed to mave passengers and goods. At some airports cargoservices have been subjected to cargo service charge (CSC) to improve service and security. Theresearch used WfP (willingness to pmj) method through questionnaires and interoiews to 16 forwarderat Ngurah Rai Airport. The results of the study showed that the fonvarder willing (wi1lingnessto pmj) to pay cargo seruice charge with a range of value of Rp240, - to Rp395, - and 54.55% ofservice users to judge the level of service (level of service) provided biJ the management of cargo hasthe good criterill. It is recommended that the establishment of CSC refers to the futuring poliaJ tomake it enforceable and CSC's revenue at Ngurah Rai Airport can be used to imprave cargo services.Keywords: willingness to pay, Cargo Service Charge, forwarder